2023
DOI: 10.20517/energymater.2023.48
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids and their derivatives for lithium batteries: role, design strategy, and perspectives

Matteo Palluzzi,
Akiko Tsurumaki,
Henry Adenusi
et al.

Abstract: Lithium-ion batteries (LIBs) are the predominant power source for portable electronic devices, and in recent years, their use has extended to higher-energy and larger devices. However, to satisfy the stringent requirements of safety and energy density, further material advancements are required. Due to the inherent flammability and incompatibility of organic solvent-based liquid electrolytes with materials utilized in high energy devices, it is necessary to transition to alternative conductive mediums. The foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…In response to these challenges, research endeavors are shifting towards developing safer alternatives to liquid electrolytes, with a focus on solid-state batteries (SSBs). [7][8][9] To mitigate the limitations linked with liquid electrolytes and enhance the security of Li metal anodes, pure solid electrolytes (SEs) have emerged as a promising solution.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these challenges, research endeavors are shifting towards developing safer alternatives to liquid electrolytes, with a focus on solid-state batteries (SSBs). [7][8][9] To mitigate the limitations linked with liquid electrolytes and enhance the security of Li metal anodes, pure solid electrolytes (SEs) have emerged as a promising solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported several brand-new methods, among which the use of ionic liquids to modify solid electrolytes to obtain “ionic gel electrolytes” has attracted widespread attention . Ionic liquids (ILs) have noncombustion, nonvolatility, high thermal stability, and a broad electrochemical stability window. Ionic gel electrolyte (IGE) using an ionic liquid as a plasticizer can largely avoid the risk of using organic solvent, which is considered a kind of safe electrolyte system with great application potential. , …”
Section: Introductionmentioning
confidence: 99%
“…26−28 Ionic gel electrolyte (IGE) using an ionic liquid as a plasticizer can largely avoid the risk of using organic solvent, which is considered a kind of safe electrolyte system with great application potential. 29,30 But traditional polymer matrices, such as PAN and PVDF, only have limited IL content. To maximize the benefits of ILs, it is significant to select the appropriate matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state lithium batteries are considered promising candidates for next-generation secondary batteries as they can perfectly balance the constantly increasing demand for battery energy density and safety. 1–5 Various types of solid-state electrolytes (SSEs) have been proposed and developed, yet many concerns still remain in terms of the transition of electrolytes from the liquid to solid state, severely hindering the commercialization of solid-state batteries, with key issues including low σ at room temperature, poor electrolyte/electrode interface compatibility, and narrow electrochemical stability window. Benefiting from the excellent toughness and strength of polymers, SPEs with better fabrication and mechanical flexibility are considered interfacial friendly and more compatible with existing lithium battery production processes, and are thus considered one of the most commercially viable options.…”
Section: Introductionmentioning
confidence: 99%